PENGARUH PREPARASI DAN TINGKAT SUBSTITUSI UWI UNGU (Dioscorea alata L.) TERHADAP SIFAT FISIK, KIMIA DAN TINGKAT KESUKAAN BOBA PATI SAGU (Metroxylon sagu) - Aidah Maryuniati; Siti Tamaroh Cahyono Murti (Universitas Khairun, 2023)
The potential of purple yam (Dioscorea alata L.) as a source of natural antioxidants has not been optimally utilized by the community. So there is a need for innovation in the utilization of purple yam through food diversification. Sago starch has amylose and amylopectin content similar to tapioca. So that in this study we wanted to develop boba with the basic ingredients of sago starch and the addition of purple yam. This study aims to produce boba that has antioxidant activity and is liked by panelists from variations in purple yam preparation and the use of sago starch on physical, chemical properties and preference level. This study used two preparation methods, namely steaming and boiling with variations in the concentration of sago and purple yam puree 48g:12g, 42g:18g and 36g:24g. Bubble pearl was tested for color, moisture content, antioxidant activity, anthocyanin content, liking test and selected samples were tested for total phenol content and ash content. The experimental design used was a complete randomized design with 2 factorials and the data were statistically tested using Univariate Analysis of Variance and ANOVA, if there was a significant difference, followed by DMRT test with Î±=0,05. The results showed that the preparation method and concentration of sago starch and purple yam puree had a significant effect on the increase in antioxidant activity and anthocyanin content. The selected boba that was favored by panelists was boba with steaming treatment with a concentration of sago starch and purple yam puree of 34g:24g with a moisture content of 67,12% bb, antioxidant activity of 59,54% RSA, anthocyanin content of 8,45 mg/g bk, total phenols of 30,46 mg GAE/g bk, and ash content of 0,02% bk. Â Keywords : purple yam puree, antioxidant, bobaÂ